Diferenças de gênero nas disfunções temporomandibulares : revisão sistemática e metanálise - Bueno, Caroline Hoffmann (2017)
Purpose: The aim of the study was to evaluate the existence of gender differences in the temporomandibular disorders based on the literature. Methods: A systematic review was performed in PUBMED, EMBASE, WEB OF SCIENCE and LILACS, no restrictions on the year. The search was conducted by two reviewers independently and in duplicate. It was also performed a manual search in the references of the included studies and in the literature review articles previously published, as well as a search for gray literature. Data were analyzed quantitatively by combining the results in a meta-analysis and presenting them in a Forest Plot graph. The measure effect used was the odds ratio (OR). The quality of the articles was assessed by a questionnaire adapted from "The Newcastle - Ottawa Scale (NOS)" and publication bias through visual method with a Funnel Plot graph. Results: The electronic search in the database returned a total of 6104 articles that were analyzed according to the eligibility criteria, which we selected 112 articles for full-text reading. Through our manual search 1 study was recovered. In the end, five articles were included, with 2518 participants. Women had, for the most part, higher prevalence of TMD in diagnostic groups of RDC/TMD. It was also established by the meta-analysis an OR of 2.24 (global DTM), 2.09 (Group I), 1.6 (Group II) and 2.08 (Group III). Conclusions: In this study, we were able to show the importance of gender in the context of temporomandibular disorders, identifying it as a risk factor and indicating a 2.2 times higher risk for women to develop TMD compared to men.